Disaster education, communication and engagement - Dufty, Neil (John Wiley & Sons, Inc., 2020)
"Disasters are socially-constructed and therefore the role of at-risk people and their communities in disasters is critical. Learning by these people and their communities before, during and after a disaster is paramount. This book is about learning that aims to help keep people safe and minimise damages in disasters. It focusses on disasters emanating from natural hazards"- Resumé vydavatel
Keywords: krizový management; krizový management -- sociální aspekty; studium a výuka; přírodní katastrofy; komunity (sociologie); crisis management; crisis management -- social aspects; study and teaching; natural disasters; communities (sociology); elektronické knihy; monografie; electronic books; monographs